Pigovian transport pricing in practice - Beat Hintermann; Beaumont Maarten Schoeman; Joseph Molloy; Thomas Götschi; Alberto Castro; Christopher Tchervenkov; Uros Tomic; Kay W. Axhausen (University of Basel, Center of Business and Economics (WWZ), 2024)
We implement Pigovian transport pricing in a field experiment in urban agglomerations of Switzerland over the course of 8 weeks. The pricing considers external costs from climate damages, health outcomes and congestion and varies across time, space and mode of transport. The treatment reduces the external costs of transport of the treated individuals by 4.5% in the short run. The main underlying mechanism is a shift away from driving towards other modes, such as public transport, walking and cycling. Providing information about external costs alone changes behavior of altruists, but not for the whole sample. We estimate the welfare improvements from such a policy to be around 140 US dollars per person and year, which is twice as large as the effects of a fuel tax that generates the same revenue.
Keywords: H23; H31; I18; Q52; Q54; R41; R48; 330; Transport pricing; Pigovian taxation; mobility; external costs; congestion; tracking